Complex Spectroscopy Studies of Nifedipine Photodegradation - Mirela Paraschiv; Monica Daescu; Cristina Bartha; Bogdan Chiricuta; Mihaela Baibarac (MDPI AG, 2023)
The aim of this work is to highlight the influence of UV light on the hydrolysis reaction of nifedipine (NIF) in the presence of alkaline solutions. In this context, the photodegradation of NIF in the absence of alkaline solutions caused (a) a change in the ratio between the absorbances of three bands in the UV-VIS spectra localized at 224-240 nm, 272-276 nm and 310-340 nm, assigned to the electronic transitions of -COOCH3 groups, -NO2 groups and a heterocycle with six atoms; (b) a red-shift of the photoluminescence (PL) band from 458 nm to 477 nm, simultaneous with an increase in its intensity; (c) a decrease in the ratio of the Raman line intensities, which peaked at 1224 cm−1 and 1649 cm−1, associated with the vibrational modes of -C-C-O in the ester group and C=C stretching; and (d) a decrease in the ratio between the absorbances of the IR bands, which peaked at 1493 cm−1 and 1223 cm−1, associated with the vibrational modes of the -NO2 group and C-N stretching. These changes were explained considering the NIF photodegradation reaction, which leads to the generation of the compound 4-(2-nitrosophenyl)-2.6-dimethyl-3.5-dimethoxy carbonyl pyridine. The interaction of NIF with NaOH in the absence of UV light was demonstrated to induce changes in the vibrational mode of the -C-C-O bond in the ester group. The photodegradation of NIF after its reaction with NaOH induces significant changes highlighted in its (a) UV-VIS spectra, by the shift of the absorption band at 238 nm; (b) PL spectra, by the supraunitary value of the ratio between the emission band intensities at 394-396 nm and 450 nm; (c) Raman spectra, by the change in the ratio between the intensities of the lines that peaked at 1224 cm−1 and 1649 cm−1 from 0.61 to 0.49; and (d) FTIR spectra, by the lowered absorbance of the IR band at 1493 cm−1 assigned to the vibrational mode of the -NO2 group as a result of the generation of the nitroso compound. These changes were explained considering the hydrolysis reaction products of NIF, as the nitroso compound is converted to a lactam-type compound. The photodegradation reaction rate constants of NIF and NIF after interaction with NaOH were also reported. The decrease in thermal stability of NIF samples after interaction with NaOH, as well as of NIF after exposure to UV light compared to NIF prior to exposure to UV light, was demonstrated by thermogravimetry, and the key fragments were confirmed by mass spectrometry.